Case Report: An Unusual Presentation of Cardiovascular Involvement in Eosinophilic Granulomatosis With Polyangiitis - Li, Yajuan; Zhou, Hui; Zhou, Yaou; Tang, Haixiong (Frontiers in Cardiovascular Medicine, 2022)
Background: Because eosinophilic granulomatosis with polyangiitis (EGPA) is so rare and the symptoms so varied, it can be a challenge to get a correct diagnosis in clinical practice. Cardiovascular involvement is the main cause of death of EGPA. We are the ﬁrst to report of cardiac magnetic resonance (CMR) findings about right-sided heart involvement in EGPA. Patient Findings: The initial abnormalities detected by CMR were Löffler endocarditis with extensive thrombosis and left ventricular (LV) dysfunction. After active treatment, LV systolic function recovered and endocarditis with thrombosis significantly improved, but there was rapidly progressive pulmonary hypertension, enlargement of right atrium and right ventricle and persistent right-sided heart failure. The patient eventually died of sudden cardiac death 6 months after hospital discharge. Conclusions: Löffler endocarditis and right-sided heart involvement are both rare presentations in patients with EGPA. CMR is a reliable noninvasive tool to precisely and comprehensively assess cardiovascular involvement in EGPA.